Application of the swift method for risk assessment in the production of cottage cheese - Melnyk, Oksana; Kuzmin, Oleg; Niemirich, Oleksandra; Mamchenko, Liudmyla; Lytovchenko, Oleksandr (My University, 2023)
The quality and safety of food products in the modern world is the main component of sustainable development of food industry enterprises. The enterprises have implemented a system of preventive measures that prevents the occurrence of risks, assesses them, controls hazards in raw materials, technological processes and finished products, which significantly reduces the risks of threats to human life and health. An overall risk assessment enables decision makers and relevant parties to better understand the risks that may affect the achievement of objectives and the adequacy and effectiveness of the controls in place. This provides a basis for making decisions about the most appropriate approach to handling the risks that may arise in the manufacture of food products. Risk analysis involves consideration of the cause and sources of risk, their consequences and the likelihood of these consequences. The paper considers the methodology of «what if?» risk assessment in the production of cottage cheese. The advantages and disadvantages of this method, the process of identifying, assessing and preventing risks are presented.

Якість та безпечність харчових продуктів у сучасному світі є основною складовою сталого розвитку підприємств харчової промисловості. На підприємствах запроваджено систему профілактичних заходів, які запобігають виникненню ризиків, оцінюють їх, контролюють шкідливості в сировині, технологічних процесах і готовій продукції, що значно знижує ризики виникнення загроз життю та здоров’ю людей. Загальна оцінка ризику дозволяє особам, які приймають рішення, і відповідним сторонам краще зрозуміти ризики, які можуть вплинути на досягнення цілей, а також на адекватність і ефективність наявних засобів контролю. Це забезпечує основу для прийняття рішень щодо найбільш прийнятного підходу до поводження з ризиками, які можуть виникнути під час виробництва харчових продуктів. Аналіз ризику передбачає розгляд причини та джерел ризику, їх наслідків та ймовірності цих наслідків. У роботі розглядається методологія «що якби?» оцінка ризиків у виробництві сиру. Представлено переваги та недоліки даного методу, процес ідентифікації, оцінки та попередження ризиків.
Keywords: кафедра експертизи харчових продуктів; кафедра технології ресторанної і аюрведичної продукції; risks; product safety; swift method; cottage cheese; ризики; безпечність продукту; швидкий метод; сир